Children Under Five Year Mother Class Program to Detect the Children Growth and Development (KEMAS: Jurnal Kesehatan Masyarakat, 2018)
This research objective is to analyze the effect of children under five year mother class program to mother’s knowledge and attitude to detect the children growth and development. The research is dummy experiment with nonrandomized pretest posttest design. The research is applied to mothers having children age 0 – 59 months in Puskesmas (Community Health Service Center) Gunungsari work region as many as 30 persons. The result is there are improvement of average knowledge and attitude score after the class. Previous average score of the mothers knowledge is 0.33 point and attitude 1.8367 point. After one month of the class, average score of the mothers knowledge become 0.67 point and attitude 2.1334 point. Statistic test result that there is effect of children under five year mother class program in mother’s knowledge and attitude to detect the children growth and development. There is no effect of the class implementation to mothers knowledge and there is effect of the class implementation to mothers attitude after one month intervention.